B2M or CIITA knockdown decreased the alloimmune response of dental pulp stem cells: an in vitro study - Mingxin Hu; Yuchen Zhang; Junqing Liu; Yihan Chen; Jun Kang; Jialin Zhong; Shulan Lin; Ye Liang; Rong Cen; Xiaofei Zhu; Chengfei Zhang (Stem Cell Research & Therapy)
Abstract Background Dental pulp stem cells (DPSCs) have acquired noteworthy attention for their application in treating ischemic diseases and facilitating tissue regeneration. However, the host’s immune response following allogenic DPSC transplantation often handicaps the long-term survival of transplanted cells, thereby limiting the application of DPSCs in cell therapy. This study aims to investigate whether genetic modification can alleviate the immunogenicity of DPSCs. Methods Beta 2-microglobulin (B2M) and the class II histocompatibility complex transactivator (CIITA) were individually knocked down in DPSCs by lentiviral particles encoding short hairpin (sh) RNAs. The self-renewal capacity and pluripotency of DPSCs-shB2M (B2M silenced DPSCs) and DPSCs-shCIITA (CIITA silenced DPSCs) were evaluated by CCK8 and differentiation assays including osteogenesis, adipogenesis, and neurogenesis. The expression of HLA-I and HLA-II in DPSCs-shB2M and DPSCs-shCIITA after IFN-γ treatment were analyzed by western blotting, immunofluorescence, and flow cytometry. The function of genetically modified cells was assessed by leukocyte-mediated cytotoxicity and T-cell proliferation assays. Results Western blotting, immunofluorescence, and flow cytometry revealed that DPSCs-shB2M and DPSCs-shCIITA exhibited impaired IFN-γ inducible HLA-I and HLA-II expression. There were no significant differences in the self-renewal capacity and pluripotency among DPSCs-shB2M, DPSCs-shCIITA, and control groups (p > 0.05). Lower leukocyte-mediated cytotoxicity and higher cell survival rates were found in DPSCs-shB2M and DPSCs-shCIITA groups compared to the control (p < 0.05). T cell proliferation was significantly inhibited in both DPSCs-shB2M and DPSCs-shCIITA groups (p < 0.05). Conclusion Genetic knockdown of B2M or CIITA in DPSCs substantially reduced their immunogenicity without compromising their stemness, thereby broadening the clinical application of DPSCs in cell therapy and tissue regeneration.